Strategi Pemasaran Direct Selling Mesin Industri Sepatu Pada CV. Putra Jaya - Setiana, Neni; Ridaryanthi, Melly (MediaKom : Jurnal Ilmiah Komunikasi, 2024)
Basically, every industry, both engaged in products and services, has a goal to always live and grow. The current Industry plays an important role in producing shoes with high efficiency and quality. An effective marketing communication strategy for the shoe industry machinery becomes the key to introducing the latest technology, building relationships with shoe manufacturers, and influencing purchasing decisions, such as CVs. Putra Jaya. Marketing strategy is very influential on the sale of industrial machinery on CV. Putra Jaya. CV. Putra Jaya offers industrial machinery products to meet the needs of CV consumers. Putra Jasa attaches great importance to customer satisfaction and pays close attention to the quality of industrial machinery sales products, so that there is good governance. In the marketing strategy managed by CV. Putra Jaya is still very simple, does not have digital marketing activities like now, in CV marketing strategy activities. Putra Jaya uses Direct Selling and uses relationships from the owner. This study aimed to identify the underpinnings of direct selling in the sale of shoe industry machinery on CV Putra Jaya and analyze and find out marketing communication strategies using direct selling techniques in the sale of CV Putra Jaya shoe industry machinery in the 2021 – 2022 period. The method used here is a case study method with a qualitative approach with descriptive objectives to define how marketing communication  strategies use direct selling in shoe industry machine sales on CV Putra Jaya in the 2021 – 2022 period. Researchers conduct observations and interviews on CV. Putra Jaya. Interviews were conducted with key informants and several informants from CV. Putra Jaya. From this research, the conclusion is that’s necessary to add digital marketing to increase the existence of CV. Putra Jaya.